Mathematical assistants in differential calculus - LAZO CHONG, Edwin José (2020)
The purpose of this study is to design a reliable methodology that facilitates the learning and calculation of the derivative used in graph construction, in the determination of the tangent and normal lines to a curve and its slopes, in the calculation of velocity and acceleration. snapshots, and problems of optimization in the various fields of science, with which, it is expected, the perception and learning of the engineering student will be increased and, consequently, his academic performance will rise. All this, in view of the fact that the general intelligence factor, on which this performance depends largely, is innate and usually does not increase substantially with the development of the individual. For the current progress of this research, two algebraic assistants extracted from the internet and a program created in Excel have been used, through algorithms previously designed for this purpose. In this sense, the use of important texts outlined in the References of this article was used, concluding, finally, that the methodology created in this way, became a significant improvement in student performance. Keywords: Derivative, straight lines, speed, acceleration, optimization, mathematical wizard.